Pest Identification Guide: Melon Thrips, Thrips palmi Karny - Jeffrey D. Cluever; Hugh A. Smith (EDIS)
Melon thrips transmits Calla lily chlorotic spot virus (CCSV), Groundnut bud necrosis virus (GBNV), Melon yellow spot virus (MYSV), Tomato spotted wilt virus (TSWV), and Watermelon silver mottle virus (WSMoV). This species is primarily a foliage feeder (except in pepper and eggplant, where flowers are more preferred). Feeding on the leaves results in yellowing followed by death of leaf. Leaf feeding can also cause terminal growth to be discolored, stunted, and malformed. Feeding on fruit may cause scarring and malformed fruit. Learn to identify the melon thrips with this 2-page illustrated guide written by Jeffrey D. Cluever and Hugh A. Smith, and published by the Department of Entomology and Nematology, May 2016.